How Do Different Types of University Academics Perceive Work from Home Amidst COVID-19 and Beyond? - Rathnayake, N.M; Kumarasinghe, P.J.; Kumara, A.S. (MDPI, 2022)
The COVID-19 pandemic resulted in a massive and unintentional shift to work from home (WFH) or working remotely, as well as broad adoption of web-based platforms. The goal of this research is to uncover the attitudes to WFH among different types of academics in the Sri Lankan higher education sector. An online questionnaire survey was conducted amidst a severe COVID19 wave during June–September 2021, and 337 valid responses were received. The questionnaire contained 49 questions under four sections excluding demographic questions. The gathered data were analysed using multiple regression models.

Results of the study ascertained a significant positive attitude among academics towards online teaching (academic orientation), other than academics who from disciplines with more practical components, and there was a significant positive attitude among academics to conducting research (research orientation) while WFH. Further, the findings indicate a significant negative attitude to WFH when disseminating knowledge and engaging in community services with various stakeholders

When considering the criticality of demographics variables in the new normal, a hybrid working model can be introduced by reaping the benefits of WFH based on different types of academic orientations and their favourability towards the WFH model, rather than reverting to a full physical academic working environment. As a developing country, Sri Lanka can formulate policies on effective hybrid working models for academics to realise the potential from the lessons learned. This experience will enable the country to accomplish or move towards accomplishing the fourth goal of SDGs, quality education by 2030.
Keywords: COVID-19; hybrid work model; university academics; work from home (WFH)